2010
DOI: 10.1016/j.ccr.2010.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Leukemic IDH1 and IDH2 Mutations Result in a Hypermethylation Phenotype, Disrupt TET2 Function, and Impair Hematopoietic Differentiation

Abstract: Cancer-associated IDH mutations are characterized by neomorphic enzyme activity and resultant 2 hydroxyglutarate (2HG) production. Mutational and epigenetic profiling of a large AML patient cohort revealed that IDH1/2-mutant AMLs display global DNA hypermethylation and a specific hypermethylation signature. Furthermore, expression of 2HG-producing IDH alleles in cells induced global DNA hypermethylation. In the AML cohort, IDH1/2 mutations were mutually exclusive with mutations in the α-ketoglutarate-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

109
2,276
9
35

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,431 publications
(2,483 citation statements)
references
References 34 publications
109
2,276
9
35
Order By: Relevance
“…In support of this idea, studies have predominantly demonstrated hypermethylation signatures in both TET2-and IDH-mutant acute myeloid leukemias, 28 as well as in IDHmutant gliomas 29 and enchondromas, 32 although other authors have reported conflicting results. 41 However, although inhibition of TET function appears to be associated with DNA hypermethylation, it remains unclear how these epigenetic changes regulate gene expression, as studies have, as of yet, failed to demonstrate direct links between changes in the promoter methylation status of specific genes and alterations in the expression levels of those genes.…”
Section: -Hydroxymethylcytosine In Sdh-deficient Gistmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this idea, studies have predominantly demonstrated hypermethylation signatures in both TET2-and IDH-mutant acute myeloid leukemias, 28 as well as in IDHmutant gliomas 29 and enchondromas, 32 although other authors have reported conflicting results. 41 However, although inhibition of TET function appears to be associated with DNA hypermethylation, it remains unclear how these epigenetic changes regulate gene expression, as studies have, as of yet, failed to demonstrate direct links between changes in the promoter methylation status of specific genes and alterations in the expression levels of those genes.…”
Section: -Hydroxymethylcytosine In Sdh-deficient Gistmentioning
confidence: 99%
“…27 TET proteins are thought to have a role in tumor development, as inhibition of TET activity, as well as alteration of global DNA methylation, has been demonstrated in multiple tumor types. [28][29][30][31][32] Thus, succinate accumulation in the context of SDH deficiency could potentially drive tumorigenesis via the inhibition of TET family proteins and subsequent changes in DNA methylation and gene expression patterns. Indeed, recent work has shown that siRNA-mediated knockdown of SDHA in cultured cells and in mice leads to an inhibition of TET activity and decreased levels of 5-hmC.…”
mentioning
confidence: 99%
“…D-2HG inhibits a large family of >70 different αKG-dependent enzymes that regulate chromatin-modifications, stability of hypoxia-inducible factors, extracellular matrix maturation, and DNA repair 1 . In particular, D-2HG-mediated inhibition of chromatin-modifying enzymes impairs induction of gene expression programs required for normal cell differentiation and ‘locks’ malignant cells in an undifferentiated stem cell-like state 57 . The relative contributions of different D-2HG targets to oncogenesis likely varies depending on the cellular context 8,9 .…”
mentioning
confidence: 99%
“…Much like SDH‐ and FH‐mutated tumors, IDH‐mutated cells and tumors have been shown to exhibit a hypermethylator phenotype through the inhibition of the ten‐eleven translocation (TET) family of DNA demethylases and members of the Jumonji C‐domain histone demethylases through the competitive inhibition of αKG binding by (R)‐2HG 105, 106, 107, 108, 109. However, unlike SDH and FH mutations, the effect of (R)‐2HG on PHD activity has been the subject of some controversy.…”
Section: Mutations Of Mitochondrial (And Associated) Metabolic Enzymementioning
confidence: 99%